The Impact of Economic factors on the labour market in Kazakhstan - Abolova, L.; Koishibayeva, K.; Nassibulov, B.; Sydykov, N.; Yeraliyev, Y. (International School of Economics KAZGUU, 2023)
This study is devoted to the analysis of the impact of economic indicators on unemployment rate in Kazakhstan. The purpose of this research is to analyze how rates, especially wage, inflation rates and economic growth factors affecting the unemployment in Kazakhstan with the providing comparison with the developed and developing country. The analysis in the study carried out by using a regression model and benchmark analysis. In this study used data from 2000 to 2020 years quarterly taken from the official websites and Excel software was used as tool in the providing regression model. According to the results of the study, it was determined that the hypotheses constructed in the study, which were based on economic factors such as inflation, the level of average wages and GDP per capita, have a significant impact on unemployment in the labor market of Kazakhstan
Keywords: labour market in Kazakhstan, economic factors